Impact of Fixed Orthodontic Wire Materials on Saliva pH Levels and Flow Rates: A Clinical Investigation - Feili, Fahimeh; Abbasi Simera, Khalil; Eskandarnejad, Mahdis; Seidkhani, Hossein (Journal of Dental School, 2025)
Objective(s): This study aimed to investigate the changes in salivary pH and flow rates during fixed orthodontic treatment with nickel-titanium (Ni-Ti) and stainless steel (SS) wires. Methods: A longitudinal clinical investigation was conducted among 43 participants undergoing fixed orthodontic treatment. Salivary pH levels and flow rates were measured at three time points: before treatment (T1), one month after placement of Ni-Ti 0.016 wires (T2), and one month after placement of SS 0.016 wires (T3). Repeated-measures ANOVA was performed to analyze trends over time, and pairwise comparisons with Bonferroni adjustment were used to identify significant differences between the time points. Statistical analysis was conducted at a significance level of 0.05. Results: A significant progressive decline in salivary pH levels was observed, with mean values decreasing from 6.85 at T1 to 6.71 at T2 and 6.68 at T3 (p < 0.001). Both linear (F = 128.360, p < 0.001) and quadratic trends (F = 19.680, p < 0.001) were evident. Saliva flow rates showed a slight but significant increase after wire placement (T2: 0.375 ml; T3: 0.374 ml) compared to baseline (T1: 0.358 ml), stabilizing thereafter (p = 0.003). Pairwise comparisons revealed greater pH declines after SS wire placement compared to Ni-Ti wires (p = 0.002). Conclusions: Fixed orthodontic treatment significantly affects salivary pH levels and flow rates, with SS wires exerting a greater impact on oral acidity. These results highlight the need for preventive strategies to mitigate potential adverse effects on oral health during orthodontic treatment.